Developmental aspects of the thymus in aging - Globerson, Amiela (Advances in Cell Aging and Gerontology, 2002)
Thymic involution has been envisaged as an irreversible decline that accounts for the major manifestations of immunosenescence. However, more recent studies have demonstrated that the thymus is not subject to total deterioration. Thymic involution is subject to hormonal control, and can be modulated by a variety of experimental strategies. Analyses of recent T lymphocytes migrants from the thymus show that generation of T cells continues through old age, albeit at a reduced rate and altered patterns. In general, processes of T lymphocyte development occur in the thymus, yet, extrathymic T cell development has also been indicated and may play a compensatory role in aging. Taken together, thymocytopoiesis in aging involves multifactorial mechanisms along the bone marrow stem cell – thymus axis, associated with hormones, neuropeptides and cytokines effects. These mechanisms include basic cell aging processes (e.g. cell replication and programmed cell death), as well as processes unique to the immune system (e.g. generation of the T cell receptor repertoire and control of potentially autoreactive cells). Understanding the developmental mechanisms along this axis is crucial for strategies geared towards the assurance of a beneficial immune system in old age.